Modeling and simulation of carbon-nanocomposite-based gas sensors - Roopa Hegde; Punya Prabha V; Shipra Upadhyay; Krishna S B (Beilstein Journal of Nanotechnology)
This paper reports simulation of a carbon monoxide gas sensor using COMSOL Multiphysics whose active sensing material used is a carbon nanocomposite (i.e., 0.1 wt % of single-walled carbon nanotubes along with PEDOT:PSS (poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate)) in an equal volume ratio of 1:1. Given the high cost associated with the development of these sensors, it becomes imperative to establish a mathematical model for economically predicting their behavior. The simulation using COMSOL Multiphysics is performed to obtain the surface coverage of the sensor by introducing carbon monoxide gas through a Gaussian pulse feed inlet at concentrations ranging from 1 to 7 ppm. The surface coverage over the range of 14% to 32.94% for the given range of concentrations is achieved giving the information of the amount of gas molecules adsorbed onto the surface of the sensing material at a given time. The surface coverage of the sensor is enhanced by using the nanocomposite materials which in turn enhances the sensitivity of the gas sensors.